2020
DOI: 10.1038/s41436-019-0669-9
|View full text |Cite
|
Sign up to set email alerts
|

POLR1B and neural crest cell anomalies in Treacher Collins syndrome type 4

Abstract: Purpose: Treacher Collins syndrome (TCS) is a rare autosomal dominant mandibulofacial dysostosis, with a prevalence of 0.2-1/ 10,000. Features include bilateral and symmetrical malar and mandibular hypoplasia and facial abnormalities due to abnormal neural crest cell (NCC) migration and differentiation. To date, three genes have been identified: TCOF1, POLR1C, and POLR1D. Despite a large number of patients with a molecular diagnosis, some remain without a known genetic anomaly. Methods: We performed exome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 27 publications
1
70
0
1
Order By: Relevance
“…In addition, in 2011, mutations in two genes encoding for Pol I subunits ( POLR1D and POLR1C ) were found mutated in a small number of TCS patients [ 41 ]. More recently, the work of Sanchez et al [ 42 ] reported mutations connected with TCS also in the POLR1B gene. Therefore, all these genes are involved in ribosome biogenesis, and especially in rRNA transcription, so Treacher Collins syndrome may be rightly classified as a pure ribosomopathy.…”
Section: Pure Ribosomopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in 2011, mutations in two genes encoding for Pol I subunits ( POLR1D and POLR1C ) were found mutated in a small number of TCS patients [ 41 ]. More recently, the work of Sanchez et al [ 42 ] reported mutations connected with TCS also in the POLR1B gene. Therefore, all these genes are involved in ribosome biogenesis, and especially in rRNA transcription, so Treacher Collins syndrome may be rightly classified as a pure ribosomopathy.…”
Section: Pure Ribosomopathiesmentioning
confidence: 99%
“…Therefore, all these genes are involved in ribosome biogenesis, and especially in rRNA transcription, so Treacher Collins syndrome may be rightly classified as a pure ribosomopathy. With the help of mice and zebrafish carrying mutations for the genes involved, researchers showed that deficient ribosome biogenesis caused a reduced proliferation of the progenitors of the craniofacial skeleton cells, called neural crest cells (NCC) [ 42 , 66 , 67 , 68 ]. It is well known that impaired ribosome biogenesis triggers nucleolar stress with the stabilization of p53 and consequent apoptosis.…”
Section: Pure Ribosomopathiesmentioning
confidence: 99%
“…Of particular interest is impairment of EMT in patient cells; while likely to derive from delayed differentiation, undergoing an EMT is absolutely essential during neural crest induction as migratory capacity of NCCs is vital for vertebrate development. Defects in NCC migration have been observed in differentiated iNCCs derived from Treacher Collins syndrome (TCS) patients and in mouse models of TCS [36,37,85]. Defective NCC migration in Bardet-Biedl syndrome is thought to underlie the craniofacial phenotype, demonstrating that defective NCC migration can be pathogenic [33,86].…”
Section: Plos Onementioning
confidence: 99%
“…In vivo, induction of NCCs relies on WNT, BMP, FGF, Activin/TGF-β and Notch/Delta signalling pathways [28][29][30][31][32][33]. Given the very significant role of NCCs in the development of craniofacial structures, a number of craniofacial disorders have been associated with defects in NCC biology including Treacher Collins syndrome, CHARGE syndrome and the spliceosomal craniofacial disorders Nager syndrome (NS) and Richieri-Costa Pereira Syndrome (RCPS) [6,17,24,[34][35][36][37][38][39]. Therefore, it is likely that variants in TXNL4A in BMKS lead to defects particularly affecting NCCs, resulting in a craniofacial phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…A POLR1D-gén érintettsége esetén AD és AR öröklődésmenet is előfordulhat. Egy 2020. évi tanulmányban a POLR1B (RNA polymerase I subunit) patogén variánsait találták 6, klinikailag Treacher Collinsszindrómás beteg esetében [8]. Az EFTUD2-(elongation factor Tu GTP-binding domain-containing 2) gén eltéréseit azonosították az úgynevezett Guion-Almeida-típus esetében, mely súlyos, progresszív microcephaliával, intellektuális elmaradással, choanaatresiával, szájpadhasadékkal, szívfejlődési rendellenességekkel, valamint oesophagusatresiával jár [9].…”
unclassified